The leverage role of feedback framing in promoting the spillover effect of idle item recycling - Guo, Tingting; Zhu, Jinlei; Wu, Zhengxiang (Frontiers in Psychology, 2025)
In response to the growing concerns over resource wastage and environmental pollution caused by improper disposal of idle items, information interventions have been implemented to encourage consumers to recycle these items. While such interventions primarily aim to promote idle item recycling, they may also trigger spillover effects either enhancing (positive spillover) or diminishing (negative spillover) additional environmental or non-environmental virtuous behaviors. This research investigates the impact of feedback framing on the spillover effects of consumers’ idle item recycling behavior through three scenario experiments. The results demonstrated that compared with highlighting the positive outcomes or benefits (positive framing), feedback information focused on preventing negative consequences or costs (negative framing) would strengthen the positive spillover of consumers’ idle item recycling behavior. And spillover effects are more likely to occur from idle item recycling to other low-cost pro-environmental behaviors. Furthermore, negative framing enhances consumers’ perceived impact and pride regarding their recycling actions, which subsequently amplifies the spillover effect. However, this effect is contingent on the level of goal progress; negative framing is effective only when goal progress is low, not when it is high. This study advances the theoretical understanding of feedback framing’s role in behavioral spillovers and offers practical insights for organizations and enterprises as they attempt to effectively intervene in consumers’ idle item recycling behavior.